2015
DOI: 10.1371/journal.pone.0129094
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Trajectories of Women Undergoing Elective Cesarean Section: Effects on Body Weight and Psychological Well-Being

Abstract: BackgroundAfter cesarean section (CS), women may be at great risk for sleep disturbance, but little is known about temporal changes in their sleep patterns and characteristics. We had two aims: 1) to identify distinct classes of sleep-disturbance trajectories in women considering elective CS from third-trimester pregnancy to 6 months post-CS and 2) to examine associations of sleep trajectories with body mass index (BMI), depressive symptoms, and fatigue scores.MethodsWe analyzed data from a prospective cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 59 publications
(123 reference statements)
2
12
1
Order By: Relevance
“…There is a long history of investigation into the implications of sleep loss and sleepiness of pregnant/postpartum women [ 37 39 ]. It was explored that sleep of pregnancy/postpartum was associated with prepregnancy BMI and depressive and fatigue symptoms during third-trimester pregnancy [ 40 ]. It has been reported that infant feeding methods were not associated with objective, subjective, or sleepiness/fatigue [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a long history of investigation into the implications of sleep loss and sleepiness of pregnant/postpartum women [ 37 39 ]. It was explored that sleep of pregnancy/postpartum was associated with prepregnancy BMI and depressive and fatigue symptoms during third-trimester pregnancy [ 40 ]. It has been reported that infant feeding methods were not associated with objective, subjective, or sleepiness/fatigue [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 In 1 study, researchers found sleep disturbances peaked on postpartum day 1 through the first week, with slowly decreasing levels of exhaustion over 1 to 6 months. 49 In another study, researchers found that the mean sleepiness levels were highest at 1 month and that 50% of the study subjects reported excessive sleepiness at 18 weeks. 50 Fathers experienced higher levels of measured sleepiness than mothers and, in some instances, had a higher propensity for falling asleep than mothers.…”
Section: Sleep Sciencementioning
confidence: 94%
“…In studies on parents, it was found both mothers and fathers have critically high levels of fatigue after the birth of an infant. [43][44][45][46][47][48][49][50][51] Assuming care responsibilities for a newborn is associated with interrupted sleep, shorter sleep duration, subjectively poor sleep quality, high levels of reported fatigue, feelings of excessive daytime sleepiness, [43][44][45][46][47][48][49][50][51] decreased sensitivity toward the infant' s needs, 46 and impaired neurobehavioral performance. 43,52 Sleep is a complex phenomenon, and new parents start the pregnancy with their own sleep patterns, which result in different levels of restorative sleep and baseline feelings of fatigue.…”
Section: Sleep Sciencementioning
confidence: 99%
See 2 more Smart Citations